Solve the Differential Equation # x^2y'' -3x+5y=0 #?

Answer 1

# y=sqrt(x)(Acos(1/2sqrt(19)lnx) + Bcos(1/2sqrt(19)lnx)) +3/5x#

We have:

# x^2y'' -3x+5y=0 #

This is a Euler-Cauchy Equation which is typically solved via a change of variable. Consider the substitution:

# x = e^t => xe^(-t)=1#

Then we have,

#dy/dx = e^(-t)dy/dt#, and, #(d^2y)/(dx^2)=((d^2y)/(dt^2)-dy/dt)e^(-2t)#

Substituting into the initial DE we get:

# x^2((d^2y)/(dt^2)-dy/dt)e^(-2t) -3e^t+5y=0 #
# :. (d^2y)/(dt^2)-dy/dt +5y=3e^t # ..... [A]

This is now a second order linear Differentiation Equation. The standard approach is to look at the Auxiliary Equation, which is the quadratic equation with the coefficients of the derivatives, i.e.

# m^2-m+5 = 0#

We can solve this quadratic equation, and we get two complex solution:

# m=1/2(1+-sqrt(19)i) #

Thus the Homogeneous equation:

# (d^2y)/(dt^2)-dy/dt +5y=0 #

has the solution:

#y=e^(1/2t)(Acos(1/2sqrt(19)t) + Bcos(1/2sqrt(19)t))#

We now seek a Particular Solution of [A], which will be of the form:

# y = Ae^t #
Differentiating wrt #t# we get:
# y' = Ae^t #, and, ># y'' = Ae^t #

Substituting into the DE [A} we get:

# Ae^t-Ae^t+5Ae^t=3e^t #

Equating coefficients we have:

# A-A+5A=3 => A=3/5 #

Hence, the GS of [A] is the combination of the homogeneous solution and the particular solution, thus:

# y=e^(1/2t)(Acos(1/2sqrt(19)t) + Bcos(1/2sqrt(19)t)) +3/5e^t#

Now we initially used a change of variable:

# x = e^t => t=lnx #

So restoring this change of variable we get:

# y=e^(1/2lnx)(Acos(1/2sqrt(19)lnx) + Bcos(1/2sqrt(19)lnx)) +3/5e^lnx#
# :. y=e^(lnsqrt(x))(Acos(1/2sqrt(19)lnx) + Bcos(1/2sqrt(19)lnx)) +3/5x#
# :. y=sqrt(x)(Acos(1/2sqrt(19)lnx) + Bcos(1/2sqrt(19)lnx)) +3/5x#

Which is the General Solution

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To solve the differential equation (x^2y'' - 3x + 5y = 0), we can assume a solution of the form (y = x^m). Substituting this into the differential equation yields a characteristic equation in terms of (m). Solving this characteristic equation gives us the values of (m). Depending on the nature of the roots of the characteristic equation, the general solution can have different forms.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7